2003
DOI: 10.1002/tea.10086
|View full text |Cite
|
Sign up to set email alerts
|

Just do it? impact of a science apprenticeship program on high school students' understandings of the nature of science and scientific inquiry

Abstract: The purpose of this study was to explicate the impact of an 8-week science apprenticeship program on a group of high-ability secondary students' understandings of the nature of science and scientific inquiry. Ten volunteers (Grades 10-11) completed a modified version of the Views of Nature of Science, Form B both before and after their apprenticeship to assess their conceptions of key aspects of the nature of science and scientific inquiry. Semistructured exit interviews provided an opportunity for students to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
2
30

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(249 citation statements)
references
References 38 publications
(37 reference statements)
12
194
2
30
Order By: Relevance
“…In these treatments, science is commonly described in universalist terms, as an enterprise that has the ability to produce reliable, objective knowledge about the natural world through the rigorous application of its methods (see, for example, Holt Science and Technology, 2001;Spaulding & Namowitz, 2003;and Wysession, Frank, & Yancopoulos, 2004). This view of science as the search for durable knowledge is consistent with the characterizations of science offered in the recent standards documents, and conforms as well to the descriptions offered by some in the science education research community (Bell et al, 2003;Cobern & Loving, 2001;Smith & Scharmann, 1999;Southerland, 2000). Recent research from the field of science studies, however, has shown that objective truths about the world are not as easily obtained as these descriptions suggest.…”
Section: The Current Trendsupporting
confidence: 85%
“…In these treatments, science is commonly described in universalist terms, as an enterprise that has the ability to produce reliable, objective knowledge about the natural world through the rigorous application of its methods (see, for example, Holt Science and Technology, 2001;Spaulding & Namowitz, 2003;and Wysession, Frank, & Yancopoulos, 2004). This view of science as the search for durable knowledge is consistent with the characterizations of science offered in the recent standards documents, and conforms as well to the descriptions offered by some in the science education research community (Bell et al, 2003;Cobern & Loving, 2001;Smith & Scharmann, 1999;Southerland, 2000). Recent research from the field of science studies, however, has shown that objective truths about the world are not as easily obtained as these descriptions suggest.…”
Section: The Current Trendsupporting
confidence: 85%
“…The literature on scientist-student interactions is drawn mainly from summer school programmes and apprenticeship evaluations (Bell, Blair, Crawford, & Lederman, 2003;Bleicher, 1996;Knox, Moynihan, & Markowitz, 2003;Rahm, 2007) and focuses on how these programmes have influenced students' attitudes towards science and students' conceptual and epistemological understanding. For instance, Knox et al (2003) investigated the impact of a summer school programme at a university research facility on 14 -18-year-old students' interest in science and their perceived skills in laboratory work.…”
Section: Scientist -Student Interactionsmentioning
confidence: 99%
“…Similarly, Gibson and Chase (2002) found that students participating in a summer school programme developed more positive attitudes towards science and towards science careers compared to students who did not participate in the summer school programme. Bell et al (2003) found that 15-17-year-old students, who participated in an 8-week science apprenticeship programme working alongside scientists covering a range of science procedures including research design, data collection and data analysis, did not change their views of scientific inquiry and the nature of science (NOS) considerably. Bell et al (2003) argue that the extent to which explicit discussions about the NOS and scientists' work were taking place during these apprenticeships was vital for whether students would change or not their NOS views.…”
Section: Scientist -Student Interactionsmentioning
confidence: 99%
“…In this kind of processes, students do not need to actually think. As a result, they are not curious about exploring things, the space for imagination is limited, and the excitement of finding answers through science is reduced (Bell, Blair, Crawford, & Lederman, 2003;Chinn & Malhotra, 2002;Hickey, Kindfield, Horwitz, & Christie, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%